RATIONAL USE OF OPHTHALMIC MEDICATIONS IN PRIMARY CARE: AN APPROACH FOR GENERAL PRACTITIONERS ON PHARMACOKINETICS, IATROGENESIS, AND PRESCRIPTIVE SAFETY - Paim, Otávio Paino (Seven Editora, 2026)
Introduction: Self-medication in Brazil represents an endemic public health problem, within which topical ophthalmic medications (eye drops) occupy a critical position. Frequently underestimated as mere visual hygiene solutions and widely marketed as over-the-counter products, eye drops are highly potent medications. Their route of administration allows rapid bypass of first-pass hepatic metabolism through nasolacrimal drainage, resulting in systemic bioavailability capable of inducing clinically relevant cardiovascular and respiratory effects in susceptible patients. Objective: This chapter aims to deconstruct the fallacy of the harmlessness of eye drops and to equip the general practitioner, the principal gatekeeper of the healthcare system, for the prevention, identification, and management of ocular and systemic iatrogenic events resulting from the irrational use of these formulations. It also seeks to enable recognition of patients undergoing advanced ophthalmologic treatments (intravitreal injections, sustained-release implants, and prescribed therapies for dry eye disease) who may present to primary care with complications. Development: The chapter details the pharmacokinetics of the ocular surface and examines the main therapeutic classes. It discusses the deleterious potential of indiscriminate corticosteroid use (inducing steroid-induced glaucoma and cataracts), topical vasoconstrictors, and empirical antibiotics. At the systemic level, it explores the inadvertent toxicity of ophthalmic beta-blockers. It further addresses in depth the toxicity of benzalkonium chloride (BAK) and the transition toward preservative-free formulations, while dedicating a specific section to patients undergoing highly complex ophthalmologic treatments and how the general practitioner should approach them. Final Considerations: Mitigating morbidity associated with ophthalmic medications requires the general practitioner to adopt an active approach: rigorous inclusion of ophthalmic formulations in medication reconciliation, patient health literacy initiatives (including punctal occlusion technique), recognition of warning signs requiring immediate ophthalmologic referral, and pharmacovigilance reporting of detected systemic adverse reactions.